The Fast-Changing Arctic : Rethinking Arctic Security for a Warmer World - Brigham, Lawson (University of Calgary Press, 2013)
In this timely new book, international scholars and military professionals come together to explore the strategic consequences of the thawing of the Arctic. Their analyses of efforts by governments and defence, security, and coast guard organizations to address these challenges make timely and urgent reading. Rather than a single national perspective, The Fast-Changing Arctic brings together circumpolar viewpoints from North America, Europe and Asia for an integrated discussion of strategic military, diplomatic, and security challenges in the high North. Thoughtful analyses are included of different regions, climate issues, institutions, and foreign and security policies. This is an important book for students of international studies, political science, and northern studies. With a Foreword by the Honorable Mead Treadwell and an Afterword by Lawson W. Brigham. With Contributions By: Alun Anderson, Caitlyn Antrim, Rasmus Gjedsso Bertelsen, Lawson W. Brigham, Ian G. Brosnan, Daniel Clausen, J.G. Michael Clausen, Lassi Kalevi Heininen, Nong Hong, Rob Huebert, Henrik Jedig Jorgensen, P. Whitney Lackenbauer, Thomas M. Leschine, James Manicom, Edward L. Miles, Barry Scott Zellen, and Katarzyna Zysk.